2020
DOI: 10.31005/iajmh.v3i0.104
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Pandemics in the Americas: The Dominican Republic Programmatic Response Against a novel Coronavirus (COVID-19)

Abstract: The newly introduced severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causative agent of coronavirus disease 2019 (COVID-19) was confirmed in the Dominican Republic on the 29thof February 2020. Dominican Republic’s COVID-19 response is a hybrid of previous experiences in other latitudes, based on epidemiological characteristics of individuals, clinical progression of COVID‐19, and quarantine intervention reinforced by the authority. Prevention against SARS-CoV-2 in the DR had involve massive disinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…After the first case was identified in Wuhan, China, in late December 2020, the virus was first reported in La Hispaniola on 28 February 2020, with an expanding wave of transmission all over the Dominican Republic ( 3 5 ). The first cases in the country were detected in Greater Santo Domingo (which includes the capital city and the neighboring province) and San Francisco de Macoris, a north-central town in the Duarte Province ( Fig.…”
Section: Announcementmentioning
confidence: 99%
“…After the first case was identified in Wuhan, China, in late December 2020, the virus was first reported in La Hispaniola on 28 February 2020, with an expanding wave of transmission all over the Dominican Republic ( 3 5 ). The first cases in the country were detected in Greater Santo Domingo (which includes the capital city and the neighboring province) and San Francisco de Macoris, a north-central town in the Duarte Province ( Fig.…”
Section: Announcementmentioning
confidence: 99%
“…The Dominican Republic has implemented prevention and management programs for vector-borne infectious diseases like Dengue, Zika, and Chikungunya for many years (1,2). This experience notwithstanding, the most recent Global Health Security Index (GHS) report (3) ranked the Dominican Republic in its lowest tier due to its poor capability to prevent and mitigate emerging pathogens.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Strategies involving community-based seroprevalence monitoring should preclude syndromic case identification. 1 , 16 Because our study follows seroprevalence intervention in already identified hotspots by symptomatic surveillance and contact tracing, we can assume that the differences in antibody proportions in young populations suggest important pathogen circulation before community detection and intervention. We consider that an essential limitation to our study is the lack of pre-intervention serodata, and assay-related specificity/sensitivity; this might limit our understanding of any specific age-groups that may act as transmission pockets of the SARS-CoV-2 pathogen before the emergence of the hotspot.…”
mentioning
confidence: 97%
“…The Dominican Republic reported its first confirmed case of SARS-CoV-2 on March 1, 2020. 1 As of July 23, the country had reported 57,615 confirmed cases, with 29,704 of those still active cases and a total of 1,006 deaths. 2 The Dominican Republic’s health response against this pathogen consisted of strict limitations of commercial activities, suspension of in person instruction in schools and universities, and nighttime curfews starting on March 19.…”
mentioning
confidence: 99%
See 1 more Smart Citation